If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2y = 14 + -3x Solving -2y = 14 + -3x Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Divide each side by '-2'. y = -7 + 1.5x Simplifying y = -7 + 1.5x
| 5+3x=11+3x | | x=-5y+33 | | 5(m+2)=-4-8 | | 8x-22=4x+2 | | x^4+9x^2+20=0 | | 3y-10x=34 | | -4y-5x=-27 | | 4x+20=2x | | x^2-6x+58=0 | | (2x+3)(x-1)=0 | | (x+3)(x-2)=0 | | -2y-3=15 | | -2y-10=2 | | -9x-2=-38 | | -10y-1=99 | | -4x+5=17 | | 6b-5=4b+9 | | 8x-4=-12 | | -4y+5=9 | | -5x+9=54 | | 1y-4=4 | | -5y+7=47 | | -1x+2=11 | | x^2-y^2= | | -8x+9=1 | | -8y+8=88 | | -9x-4=86 | | 4x^3+4=0 | | -1y+5=1 | | -7x-8=27 | | -9y-10=-19 | | 9x-7=47 |